2020
DOI: 10.1016/s1473-3099(20)30084-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative continuation of antibiotic prophylaxis on the incidence of surgical site infection: a systematic review and meta-analysis

Abstract: Background Antibiotic prophylaxis is frequently continued for 1 day or more after surgery to prevent surgical site infection. Continuing antibiotic prophylaxis after an operation might have no advantage compared with its immediate discontinuation, and it unnecessarily exposes patients to risks associated with antibiotic use. In 2016, WHO recommended discontinuation of antibiotic prophylaxis after surgery. We aimed to update the evidence that formed the basis for that recommendation.Methods For this systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
75
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 41 publications
(55 reference statements)
6
75
2
5
Order By: Relevance
“…13 Since the risk of SSI in most clean operations is low, SAP is not recommended in such procedures. 14,15 However, in clean procedures such as breast cancer operations, SAP is recommended. 36 In the present study, more than half (62.2%) of the patients who had clean wound received prophylaxis, while nearly all (96.3%) of the patients who had clean-contaminated wound and all the patients who had contaminated wound received antimicrobial prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Since the risk of SSI in most clean operations is low, SAP is not recommended in such procedures. 14,15 However, in clean procedures such as breast cancer operations, SAP is recommended. 36 In the present study, more than half (62.2%) of the patients who had clean wound received prophylaxis, while nearly all (96.3%) of the patients who had clean-contaminated wound and all the patients who had contaminated wound received antimicrobial prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Since the risk of SSI in clean wounds which do not involve insertion of implants is low, the use of SAP is controversial. 14,15 Critical aspects of SAP administration are: giving the appropriate antimicrobial agent in adequate dose, proper preoperative prophylaxis timing, and maintaining drug level throughout the operation. 16 Different guidelines for the prevention of SSI have been developed by the American Society of Health-System Pharmacist (ASHP), World Health Organization, 17 Centers for disease control (CDC) and Healthcare Infection Control Practices Advisory Committee, and the National Institute for Clinical Excellence.…”
Section: Introductionmentioning
confidence: 99%
“…35 Most recently, a systematic review with meta-analysis of 52 RCTs (n = 19,273 participants across multiple surgical procedure types) demonstrated that no significant benefit (SSI reduction) accrued from prolonging SAP (in comparison to no postoperative doses), with a pooled RR of 0.89 (95% CI, 0.79-1.00). 36 Multiple recent studies advocate for a well-powered, randomized, prospective trial comparing infection outcomes using singleand multiple-dose SAP regimens for TKJR. 30,35,37,38 Importantly, Duke University and the AAHKS are conducting a multicenter clinical trial (estimated n = 8,000) comparing single dose and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even one additional dose of surgical prophylaxis in a child is associated with a sixfold increased risk for CDI [9]. Further, this overprescribing has not reduced the amount of post-operative complications in clean and clean contaminated surgical cases [11].…”
Section: Introductionmentioning
confidence: 99%